Effect of Nano-Silica in high performance concrete. (2021) - Vivek, D.; Elango, K.S.; Saravanakumar, R.; Mohamed Rafek, B.; Ragavendra, P.; Kaviarasan, S.; Raguram, E.
Abstract: This research work presents effect of nano silica (NS) and fly ash (FA) on properties of high performance has been addressed. Three High performance concrete (HPC) series has been designed having a total binder content of 550 kg/m 3 and at water to binder ratio (W/B) of 0.33 were adopted. This study evaluates addition of Nano silica (NS), were added in four percentages (1%, 2%, 3%, 4%) of weight of cementitious materials. The results proved that Nano silica acts as perfect filler material which helps in filling up pores and accelerates hydration process. On the other hand due to pores filling effect of Nano Silica which creates a denser material and results revealed that addition of Nano Silica has greater pore filling tendency. Usage of nano scale properties such as Nano Sio2 can result in dramatically improved properties from conventional grain size materials of same chemical composition. Nano Silica as a replacement for Ordinary Portland Cement up to 3% weight could accelerate C-S-H gel formation at early stage of hydration adversely increases resistance to water permeability of concrete specimens.